2020
DOI: 10.3390/nu12102954
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Alleviates Ferroptosis of Pancreatic β Cells in Type 2 Diabetes

Abstract: (1) Background: Pancreatic iron deposition has been found in the progression of type 2 diabetes (T2DM); however, whether ferroptosis contributes to the dysfunction of pancreatic β cells (PBC) remains enigmatic. Moreover, the potential protective effect of quercetin is also elusive; (2) Methods: T2DM mice model was established by multiple low dose streptozocin (STZ) injection, after which quercetin was intervened for 4 months; (3) Results: Substantially normalized glucose tolerance, diabetic symptoms, homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(141 citation statements)
references
References 35 publications
(38 reference statements)
6
135
0
Order By: Relevance
“…Glei et al (2002) confirmed through experiments that quercetin might reduce the risk of colon cancer by protecting the oxidative damage to DNA induced by iron. Li et al (2020) approved that quercetin lowered the iron level particularly in the islet in type 2 diabetes (T2DM) mice and abolished partially oxidative stress in pancreatic tissue. In addition, clinical Zhen et al (2013) experiments (Sajadi Hezaveh et al, 2019) indicated that quercetin could significantly reduce the saturation of high-sensitivity C-reactive protein, iron, ferritin, and Tf saturation, and increase Tf.…”
Section: Quercetinmentioning
confidence: 99%
“…Glei et al (2002) confirmed through experiments that quercetin might reduce the risk of colon cancer by protecting the oxidative damage to DNA induced by iron. Li et al (2020) approved that quercetin lowered the iron level particularly in the islet in type 2 diabetes (T2DM) mice and abolished partially oxidative stress in pancreatic tissue. In addition, clinical Zhen et al (2013) experiments (Sajadi Hezaveh et al, 2019) indicated that quercetin could significantly reduce the saturation of high-sensitivity C-reactive protein, iron, ferritin, and Tf saturation, and increase Tf.…”
Section: Quercetinmentioning
confidence: 99%
“…78 Quercetin may have a beneficial effect on type 2 diabetic patients by inhibiting iron deposition in the pancreas and effectuating iron death of pancreatic β-cells. 79 Clinical studies have shown that serum iron metabolism indexes (iron, ferritin, and transferrin saturation) and insulin resistance index (HOMA-IR) in patients with gestational diabetes were higher than in the control group, and regression analysis indicated that serum ferritin and Tf saturation were significantly positively correlated with HOMA-IR index. 80 A longitudinal and retrospective study encompassing 111 type 2 diabetic patients with kidney diseases showed that the iron accumulation confirmed by biopsy in renal tubular epithelial cells of patients with diabetic nephropathy was higher than that in the control group.…”
Section: Molecular Mechanisms Of Non-enzymatic Glycated Tf In Diabetes and Diabetic Complicationsmentioning
confidence: 99%
“…The T2DM model in rats, induced by a high-fat diet and low-dose STZ, approximately embodies the metabolic characteristics of human T2DM, and results in enduring and steady hyperglycemia [46,47]. We successfully built a T2DM model with lighter body weight and higher blood glucose levels due to the pancreatic β-cell dysfunction induced by STZ [48]. Our research also indicated impaired implant stability and reduced microstructure of the trabecula, as well as decreased osseointegration around the implants in the T2DM group, which is also in agreement with previous studies in this related field [32,49].…”
Section: Discussionmentioning
confidence: 99%